Trust in Institutions and the COVID-19 Threat: A Cross-Sectional Study on the Public Perception of Official Recommendations and of Othering in Switzerland - Ingrid Gilles; Marie-Annick Le Pogam; Margaux Perriraz; Adrian Bangerter; Eva G. T. Green; Christian Staerklé; Franciska Krings; Pascal Wagner-Egger; Isabelle Peytremann-Bridevaux (Frontiers Media S.A., 2022)
Objectives: To explore how perceived disease threat and trust in institutions relate to vaccination intent, perceived effectiveness of official recommendations, and to othering strategies.Methods: We conducted a cross-sectional survey of Swiss adults in July 2020. Outcome variables were vaccination intent, perceived effectiveness of official recommendations and othering strategies (labelling a given social group as responsible for the disease and distancing from it). Independent variables were perceived disease threat, trust in various institutions, perceived health-related measures, and sociodemographic variables. Linear and logistic regressions were performed.Results: The response rate was 20.2% (1518/7500). Perceived disease threat and trust in medical/scientific institutions were positively associated with vaccination intent and perceived effectiveness of official recommendations for coronavirus mitigation measures. Only disease threat was associated with a perception of effectiveness among othering strategies. Age and education levels were associated with vaccination intent.Conclusion: Reinforcing trust in medical/scientific institutions can help strengthen the perceived effectiveness of official recommendations and vaccination. It however does not prevent adherence to ineffective protecting measures such as othering strategies, where decreasing perceptions of epidemic threat appears to be more efficient.